2012
DOI: 10.1007/s11019-012-9426-4
|View full text |Cite
|
Sign up to set email alerts
|

Models of occupational medicine practice: an approach to understanding moral conflict in “dual obligation” doctors

Abstract: In the United Kingdom (UK), ethical guidance for doctors assumes a therapeutic setting and a normal doctor-patient relationship. However, doctors with dual obligations may not always operate on the basis of these assumptions in all aspects of their role. In this paper, the situation of UK occupational physicians is described, and a set of models to characterise their different practices is proposed. The interaction between doctor and worker in each of these models is compared with the normal doctor-patient rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…It is based on three different models describing the interaction between doctor and worker, compared with the normal DPR, focusing on different levels of trust required, possible power imbalance and the fiduciary obligations [54]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on three different models describing the interaction between doctor and worker, compared with the normal DPR, focusing on different levels of trust required, possible power imbalance and the fiduciary obligations [54]. …”
Section: Resultsmentioning
confidence: 99%
“…Even though a growing body of literature highlighted the implications for ethics of OHPs reflecting the changing nature and conditions of work [2,3,4,5,6,7,9,10,11], demographic swifts [70,71] and technological innovation [54,72,73,74,75,76,77,78,79,80], we found that the studies about the procedures for addressing ethical issues in occupational health practice are still few [53]. Most studies concern the analysis of ethical choice in business and by an individual perspective [52] without considering, as rightly stated by Westerholm, the combination of social civic values, professional values and personal values [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dutch GP guidelines often do not mention information about 'work' in general or about arrangements to promote reintegration, like work modification. [6] Therefore, guidelines should be adapted to help GPs with these tasks and the EMR may need to be provided with applications that make it easier to record occupational information. Advice concerning work should also be well documented in the EMR, to prevent patients receiving conflicting advice when they have access to more GPs.…”
Section: Implications For Practicementioning
confidence: 99%
“…Promotion of healthy working habits and working conditions and prevention of work-related diseases are considered to be tasks of OPs, but not all working patients have access to an OP. [6,7] GPs can act in an intermediary role if access to an OP is not readily available. GPs can advise patients with self-limiting diseases or chronic diseases how to continue working and thus support a healthy lifestyle, social participation and a sense of well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, OHPs have very different roles and functions, sometimes in a 'quasi-therapeutic' relationship, and at other times in a very arm's length one, especially when advising whether a particular pension fund's medical criteria for ill-health retirement have been satisfied. 5 I have previously argued that the ethical guidance in those different roles should be different, but the current edition of the FOM guidance does not address this. For example, when the OHP is required to be completely independent when advising pension funds, this requirement for the worker to see the OHP report first (and consent to its release) is 'akin to a judge offering a defendant first sight of his judgment, and requiring the defendant's consent before delivering it'.…”
mentioning
confidence: 99%